The Critical Analysis of Some Comparative Eastern Africa Corporate Governance Standards After Financial Crisis, Corporate Scandals and Manipulation - Ngoc Huy, Dinh Tran (International Journal For Research In Business, Management And Accounting, 2021)
Even though corporate scandals and bankruptcy in US and Europe and Asia show some certain evidence on weak corporate governance, weak internal control system and weak audit, Global corporate governance forum noted corporate governance has become an issue of worldwide importance. Therefore, this paper chooses a different analytical approach and among its aims is to give some systematic opinions. First, it classifies Eastern Africa representative corporate governance (CG) standards into two (2) groups: Malawi and Kenya latest CG principles covered in group 1 and, group 2, including corporate governance guidelines from EVCA 2005, so-called relative good CG group, while it uses ACCA and CFA principles as reference. Second, it , through analysis, shows differences between above set of standards which are and have been used as reference principles for many relevant organizations. Third, it establishes a selected comparative set of standards for Eastern Africa representative corporate governance system in accordance to international standards. Last but not least, this paper covers some ideas and policy suggestions.